Service Quality and Consumer’s Trust Using PT. JNE Gorontalo Branch - Hapsawati Taan (AIBPM Publisher, 2019)
Increasing quality of services increasingly gets the attention of companies to increase supply to consumers. The purpose of this study is to find out and analyze: 1) Effect of service quality on consumer decisions, 2) Effect of trust in consumer decisions, 3) Effect of service quality and trust simultaneously on consumer decisions. The sampling method uses non-probability sampling with the accidential sampling technique with a total sample of 96 people. The unit of analysis is consumers who use the services of PT. Gorontalo Branch JNE. Data collection is done through observation and questionnaires. Data were analyzed quantitatively by using multiple regression analysis techniques with SPSS 21 statistical program. The results showed that trust had a significant effect on consumer decisions. Service quality and trust have a simultaneous influence on consumer decisions. The interesting finding from the results of this study is that service quality has no significant effect on consumer decisions. This shows that the quality of service is good, not necessarily consumers decide to use these services. Suggestions / recommendations, the need for companies to improve tangible and assurance indicators related to the availability of facilities and infrastructure in service and attention to guarantees for consumer goods.